(untitled) (Journal of Partial Differential Equations, 1990)
In this paper we study the existence theorem for solution of the nonlinear degenerate oblique boundary value problems for second order fully nonlinear elliptic equations F(x, u, Du, D&sup2u) = 0 x &#8712 &#937, G(x, u, D, u) = 0, x &#8712 &#8706&#937 where F (x, z, p, r) satisfies the natural structure conditions, G (x, z, q) satisfies G_q &#8805 0, G_x &#8804 - G_0 < 0 and some structure conditions, vector &#964 is nowhere tangential to &#8706&#937. This result extends the works of Lieberman G. M., Trudinger N. S. [2], Zhu Rujln [1] and Wang Feng [6].